Pengaruh Optimalisasi Alokasi Portofolio Investasi dan Stabilitas Kinerja Perusahaan terhadap Kesejahteraan Karyawan Di PT X - Eneng Ani Rahayu; Farida Yuliaty; Vip Paramarta (Jurnal Sosial Teknologi, 2026)
This study aims to analyze the effect of investment portfolio allocation optimization and corporate performance stability on employee well-being at PT X, a reinsurance brokerage company. The research background is based on the importance of investment management and operational stability in creating sustainable value while enhancing human resource welfare. This study employed a quantitative method using descriptive analysis and multiple linear regression, with primary data collected from a survey of 25 employees. The results show that the investment portfolio allocation is categorized as moderate (54.33%) with a positive and significant effect on employee well-being (coefficient 1.322). In contrast, corporate performance stability, also in the moderate category (57.31%), has a negative but insignificant effect (coefficient -0.146). Simultaneously, both variables significantly affect employee well-being with a significance value of 0.000 and an R-square of 0.981, indicating that 98.1% of the variation in employee well-being is explained by the model. The findings conclude that investment portfolio optimization is the dominant factor in improving employee well-being. Meanwhile, corporate performance stability strategies need to be reconsidered to avoid work pressure that may reduce employee welfare. The integration of investment strategy and performance management oriented toward employee well-being is the key to corporate sustainability